Analysis of the directions of impact of the organizational culture on the activities of transport enterprises (Transport systems and technologies, 2020)
In the face of a protracted management crisis, JSC «Ukrainian Railways» loses its attractiveness to investors and its overall management. One of the directions of the strategy of the situation is to use the labor potential effectively. The authors of the article consider the influence of organizational culture on the activity of railway enterprises. The impact of corporate culture on internal regulatory processes, decision-making processes, organizational behavior, competitiveness, and overall performance of the organization. The authors describe a generalized scheme of the influence of organizational culture on the global activities of organizations.
Keywords: organizational culture, organizational behavior, JSC «Ukrainian Railways», motivation, socialization, involvement.